The effect of carbohydrate-loading and carbohydrate ingestion on fuel substrate kinetics during prolonged cycling - Bosch, Andrew Norman (MRC/UCT RU for Exercise and Sport Medicine, 2017)
It has been well established that both carbohydrate-loading before and carbohydrate ingestion during exercise can enhance endurance performance by supplying carbohydrate for oxidation. However, the precise mechanism(s) underlying the proposed ergogenic effects of these procedures remain to be established. The studies in this thesis were therefore designed to examine the effects of carbohydrate-loading and carbohydrate ingestion on fuel substrate kinetics.